Silicon-carbon negative electrode material and preparation method thereof, negative electrode plate and secondary battery
By depositing silicon germanium alloy on the porous carbon framework and forming a carbon cladding layer, the problem of volume expansion and low conductivity of silicon carbon anode material during the deintercalation of lithium is solved, and a silicon carbon anode material with high conductivity and excellent cycle life is achieved, which significantly improves the performance of the secondary battery.
Patent Information
- Application Number
- CN202411996547.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
The volume expansion of existing silicon-carbon anode materials during the deintercalation of lithium leads to poor cycle life and low conductivity, which affects the performance of secondary batteries.
A porous carbon framework is used as the core, and a silicon germanium alloy is deposited by vapor deposition method, and a carbon cladding layer is formed on its surface to form a silicon carbon negative electrode material with high conductivity and excellent cycle life.
The conductivity and rate performance of silicon carbon anode material is improved, the agglomeration and growth and isolation of silicon are avoided, and the cycle life and overall performance of secondary batteries are significantly improved.
Smart Images

Figure CN119890258A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a silicon-carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art
[0002] As one of the important components of secondary batteries, negative electrode materials have a great impact on the capacity and cycle life of secondary batteries. At present, the negative electrode material of secondary batteries is mainly graphite, but in order to further improve the capacity, rate and other performance of secondary batteries, the development of a new generation of negative electrode materials is indispensable.
[0003] Among them, silicon negative electrode materials have attracted wide attention due to their extremely high theoretical specific capacity. However, silicon negative electrodes will undergo huge volume expansion during the process of lithium insertion and extraction, resulting in poor cycle life and has never been able to be applied on a large scale. After a period of development, silicon negative electrode materials have evolved from sand-ground silicon carbon and silicon oxygen to the current vapor-deposited silicon carbon. Vapor-deposited silicon carbon negative electrode materials balance high capacity and expansion problems because they nano-size the silicon negative electrode and evenly disperse it in a porous carbon skeleton. They are considered to be the most promising silicon carbon negative electrode material technology in the future. However, as a semiconductor material, silicon itself has low electrical conductivity. After being nano-sized and dispersed in a porous carbon skeleton, it affects the overall electrical conductivity. Therefore, the electrical conductivity of vapor-deposited silicon carbon negative electrode materials is low. At the same time, silicon will still undergo a large volume expansion during the process of lithium insertion and extraction, resulting in problems such as agglomeration growth and isolation, which affect the cycle life and thus the performance of secondary batteries. Summary of the invention
[0004] Based on this, it is necessary to provide a silicon-carbon negative electrode material and its preparation method, a negative electrode sheet and a secondary battery to address the above problems. The silicon-carbon negative electrode material has high electrical conductivity and excellent cycle life, and the secondary battery using the silicon-carbon negative electrode material has better performance.
[0005] A silicon-carbon negative electrode material comprises a core and a carbon coating layer coating the core, wherein the core comprises a porous carbon skeleton and a silicon-germanium alloy distributed in the porous carbon skeleton, and the silicon-germanium alloy contains no germanium agglomerates.
[0006] In one of the embodiments, the mass ratio of silicon to germanium in the silicon-germanium alloy is 20:80-99.5:0.5.
[0007] In one embodiment, the mass fraction of the silicon-germanium alloy in the silicon-carbon negative electrode material is 20%-70%;
[0008] And / or, the mass fraction of the carbon coating layer in the silicon-carbon negative electrode material is 1%-10%.
[0009] In one embodiment, the specific surface area of the porous carbon skeleton is 300 m 2 / g-2500m 2 / g, pore volume is 0.4m 3 / g-1.5cm 3 / g.
[0010] A method for preparing the silicon-carbon negative electrode material, the method comprising:
[0011] The porous carbon skeleton is subjected to vapor deposition in an atmosphere containing a silicon source and a germanium source to obtain an inner core, wherein the germanium source comprises at least germanium chloride;
[0012] The core is carbon coated to obtain a silicon-carbon negative electrode material.
[0013] In one embodiment, the silicon source is selected from silane;
[0014] And / or, the germanium source is selected from germanium chloride, or, the germanium source is selected from germanium chloride and germane.
[0015] In one embodiment, the temperature of the vapor deposition is 300°C-700°C.
[0016] In one embodiment, the inner core is carbon-coated by chemical vapor deposition, wherein in the step of chemical vapor deposition, the gaseous carbon source is selected from at least one of acetylene, ethylene, propylene, methane, and ethane, and the temperature of chemical vapor deposition is 500°C-1000°C.
[0017] A negative electrode sheet, wherein the negative electrode active material of the negative electrode sheet is the silicon-carbon negative electrode material.
[0018] A secondary battery uses the negative electrode sheet.
[0019] In the silicon-carbon negative electrode material of the present invention, a silicon-germanium alloy is formed by germanium and silicon, and the distribution uniformity of germanium in the silicon-germanium alloy is controlled. First, the electrical conductivity of germanium is about 4 orders of magnitude higher than that of silicon, which can effectively improve the electrical conductivity of the silicon-carbon negative electrode material. Secondly, the lithium ion conductivity of germanium is 400 times higher than that of silicon, which can effectively improve the rate performance of the silicon-carbon negative electrode material. Furthermore, when germanium is uniformly dispersed in the silicon-germanium alloy, it can play a pinning role in the silicon expansion process, avoiding the agglomeration and growth of silicon and the generation of isolated silicon, and improving the cycle life. Therefore, the secondary battery using the silicon-carbon negative electrode material has better performance, especially the rate performance and cycle life.
[0020] In addition, in the preparation method of the present invention, a silicon-germanium alloy is deposited in a porous carbon skeleton by a vapor deposition method, which is beneficial to the uniformity of mixing germanium and silicon. Moreover, the present invention uses germanium chloride as a germanium source. After the silicon source decomposes to produce nano-silicon, the nano-silicon can promote the decomposition of germanium chloride to produce nano-germanium and form a silicon-germanium alloy with the nano-silicon. In this reaction, germanium will not decompose and form alone, but must be formed in the presence of nano-silicon. Thus, this symbiotic reaction allows silicon and germanium to be mixed uniformly. At the same time, the cost of germanium chloride is much lower than that of germanium sources such as germanium ane. The present invention uses germanium chloride as a germanium source, which is low in cost and can promote industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 is the Ge element distribution diagram of Example 1;
[0023] Figure 2 is the Ge element distribution diagram of comparative example 2;
[0024] Figure 3 This is the first charge and discharge curve of Example 3. DETAILED DESCRIPTION
[0025] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0027] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0028] The silicon-carbon negative electrode material provided by the present invention includes a core and a carbon coating layer coating the core. It can be understood that the carbon coating layer can partially coat the core or completely coat the core to form a core-shell structure. In the silicon-carbon negative electrode material of the present invention, it is preferred that the carbon coating layer completely coats the core to form a core-shell structure.
[0029] The core includes a porous carbon skeleton and a silicon-germanium alloy distributed in the porous carbon skeleton, and there is no germanium agglomerate in the silicon-germanium alloy. Since the electrical conductivity of germanium is about 4 orders of magnitude higher than that of silicon, and the lithium ion conductivity of germanium is 400 times higher than that of silicon, the electrical conductivity and rate performance of the silicon-carbon negative electrode material can be effectively improved by forming a silicon-germanium alloy with germanium and controlling the uniformity of the distribution of germanium in the silicon-germanium alloy.
[0030] In addition, by forming a silicon-germanium alloy with germanium and silicon and controlling the uniformity of the distribution of germanium in the silicon-germanium alloy, it can play a pinning role during the silicon expansion process, avoid the agglomeration and growth of silicon and the generation of isolated silicon, and improve the cycle life.
[0031] Optionally, the mass ratio of silicon to germanium in the silicon-germanium alloy is 20:80-99.5:0.5, for example, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:45, 60:40, 65:35, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, 99:1, etc., or a range consisting of any two of these values, further preferably 50:50-97:3. Thus, by regulating the mass ratio of silicon to germanium in the silicon-germanium alloy, the conductivity, rate performance, cycle life and other properties of the silicon-carbon negative electrode material can be further improved.
[0032] Optionally, the mass fraction of the silicon-germanium alloy in the silicon-carbon negative electrode material is 20%-70%, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., or a range consisting of any two of these values, and more preferably 40%-55%; the mass fraction of the carbon coating layer in the silicon-carbon negative electrode material is 1%-10%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or a range consisting of any two of these values. Thus, the silicon-carbon negative electrode has the best comprehensive performance.
[0033] Optionally, the specific surface area of the porous carbon skeleton is 300 m 2 / g-2500m 2 / g, for example 300m 2 / g、500m 2 / g、800m 2 / g、1000m 2 / g、1300m 2 / g、1500m 2 / g、1800m 2 / g, 2000m 2 / g, 2300m 2 / g, 2500m 2 / g, etc., or a range consisting of any two of these values, more preferably 1000m 2 / g-2000m 2 / g, pore volume is 0.4m 3 / g-1.5cm 3 / g, for example 0.4m 3 / g, 0.5m 3 / g, 0.6m 3 / g, 0.7m 3 / g, 0.8m 3 / g, 0.9m 3 / g, 1.0m 3 / g, 1.1m 3 / g, 1.2m 3 / g, 1.3m 3 / g, 1.4m 3 / g, 1.5m 3 / g, etc.
[0034] The present invention also provides a method for preparing the silicon-carbon negative electrode material, the method comprising:
[0035] S1, vapor-depositing a porous carbon skeleton in an atmosphere containing a silicon source and a germanium source to obtain a core, wherein the germanium source comprises at least germanium chloride;
[0036] S2, carbon coating the core to obtain a silicon-carbon negative electrode material.
[0037] In step S1, a silicon-germanium alloy is deposited in a porous carbon skeleton by a vapor deposition method, which is beneficial to the mixing uniformity of germanium and silicon.
[0038] Moreover, the present invention uses germanium chloride as a germanium source, so that in the process of vapor deposition, after the silicon source decomposes to produce nano-silicon, the nano-silicon can act as a catalyst to promote the decomposition of germanium chloride to produce nano-germanium, and form a silicon-germanium alloy with the nano-silicon. In this reaction, germanium will not decompose and form alone, but must be formed in the presence of nano-silicon. Therefore, this symbiotic reaction allows silicon and germanium to be evenly mixed, and the reaction equation is as follows:
[0039] GeCl4(g)+Si=SiCl4(g)+Ge
[0040] At the same time, the cost of germanium chloride is much lower than that of germanium sources such as germanium ane. The present invention uses germanium chloride as a germanium source, which can reduce costs and promote industrial applications. Of course, during vapor deposition, germanium chloride can be used alone or mixed with germanium chloride.
[0041] Optionally, the silicon source is selected from silane, such as monosilane, disilane and the like.
[0042] Optionally, the temperature of the vapor deposition is 300°C-700°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, etc., or a range consisting of any two of these values.
[0043] After obtaining the inner core, step S2 preferably uses chemical vapor deposition to carbon coat the inner core, which can be performed in the same equipment to simplify the steps and equipment investment. Wherein, in the step of chemical vapor deposition, the gaseous carbon source is selected from at least one of acetylene, ethylene, propylene, methane, and ethane, and the temperature of chemical vapor deposition is 500°C-1000°C, such as 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc., or a range consisting of any two of these values.
[0044] It can be understood that the chemical vapor deposition steps of step S1 and step S2 of the present invention are both performed under a protective atmosphere, and the protective atmosphere is selected from an inert atmosphere such as nitrogen and argon.
[0045] The present invention also provides a negative electrode sheet, wherein the negative electrode active material of the negative electrode sheet is the silicon-carbon negative electrode material.
[0046] It can be understood that the negative electrode sheet includes a current collector and a negative electrode active material layer attached to the surface of the current collector, and the negative electrode active material layer is made of the silicon-carbon negative electrode material, a binder, a conductive agent, etc. in proportion, wherein the conductive agent is selected from at least one of acetylene black, Ketjen black or Super P, and the binder is selected from at least one of sodium carboxymethyl cellulose, sodium alginate or polyvinylidene fluoride.
[0047] The present invention also provides a secondary battery, wherein the secondary battery uses the negative electrode sheet.
[0048] It can be understood that the secondary battery can be a lithium-ion battery, etc., and also includes a positive electrode sheet, a separator, an electrolyte, etc.
[0049] Since the silicon-carbon negative electrode material of the present invention has excellent electrical conductivity, rate performance and cycle life, the secondary battery using the silicon-carbon negative electrode material has better performance, especially rate performance and cycle life.
[0050] The silicon-carbon negative electrode material and its preparation method, negative electrode sheet and secondary battery are further described below through the following specific examples. The instruments and equipment used in the following examples, unless otherwise specified, are all conventional laboratory instruments and equipment; the experimental materials used in the following examples, unless otherwise specified, can all be purchased.
[0051] Example 1
[0052] In a nitrogen atmosphere, 1 kg of 1800 m 2 / g, pore volume is 0.85cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced. The flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 2.5g / min, the deposition temperature was 500°C, and the deposition time was 192min to obtain an inner core.
[0053] Then, acetylene gas was switched to a flow rate of 3 L / min, and deposition was carried out at 620°C for 85 min to obtain a silicon-carbon negative electrode material.
[0054] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 45%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 80:20. Figure 1 As shown, germanium is evenly distributed in the silicon-germanium alloy without any germanium agglomerates.
[0055] Example 2
[0056] In a nitrogen atmosphere, 1 kg of 1800 m 2 / g, pore volume is 0.85cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced, the flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 2.5g / min, the deposition temperature was 500℃, and the deposition time was 235min to obtain the inner core.
[0057] Then, acetylene gas was introduced at a flow rate of 3 L / min, and deposition was carried out at 620°C for 93 minutes to obtain a silicon-carbon negative electrode material.
[0058] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 50%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 80:20.
[0059] Example 3
[0060] In a nitrogen atmosphere, 1 kg of 2000 m 2 / g, pore volume is 1.0cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced, the flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 2.5g / min, the deposition temperature was 500℃, and the deposition time was 235min to obtain the inner core.
[0061] Then, acetylene gas was introduced at a flow rate of 3 L / min, and deposition was carried out at 620°C for 93 minutes to obtain a silicon-carbon negative electrode material.
[0062] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 50%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 80:20.
[0063] Example 4
[0064] In a nitrogen atmosphere, 1 kg of 2000 m 2 / g, pore volume is 1.0cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced. The flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 4.0g / min, the deposition temperature was 500°C, and the deposition time was 267min to obtain an inner core.
[0065] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 103 min to obtain a silicon-carbon negative electrode material.
[0066] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 55%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 70:30.
[0067] Example 5
[0068] In a nitrogen atmosphere, 1 kg of 2000 m 2 / g, pore volume is 1.0cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced. The flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 5.8g / min, the deposition temperature was 500℃, and the deposition time was 303min to obtain an inner core.
[0069] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 116 min to obtain a silicon-carbon negative electrode material.
[0070] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 60%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 60:40.
[0071] Example 6
[0072] In a nitrogen atmosphere, 1 kg of 1300 m 2 / g, pore volume is 0.6cm 3 / g porous carbon material is placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride is introduced. The flow rate of monosilane is 3L / min, the flow rate of germanium chloride is 10.5g / min, the deposition temperature is 500℃, and the deposition time is 72min to obtain the inner core.
[0073] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 66 min to obtain a silicon-carbon negative electrode material.
[0074] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 30%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 40:60.
[0075] Example 7
[0076] In a nitrogen atmosphere, 1 kg of 1200 m 2 / g, pore volume is 0.4cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germanium chloride was introduced. The flow rate of monosilane was 3L / min, the flow rate of germanium chloride was 17.3g / min, the deposition temperature was 500℃, and the deposition time was 34min to obtain the inner core.
[0077] Then, acetylene gas was introduced at a flow rate of 3 L / min, and deposition was carried out at 620°C for 58 min to obtain a silicon-carbon negative electrode material.
[0078] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 20%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 20:80.
[0079] Example 8
[0080] In a nitrogen atmosphere, 1 kg of 1800 m 2 / g, pore volume is 0.85cm 3 / g of porous carbon material is placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane, germanium chloride and germane is introduced. The flow rate of monosilane is 3L / min, the flow rate of germanium chloride is 1.3g / min, the flow rate of germane is 0.14L / min, the deposition temperature is 500℃, and the deposition time is 184min to obtain the inner core.
[0081] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 84 min to obtain a silicon-carbon negative electrode material.
[0082] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 45%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 80:20.
[0083] Comparative Example 1
[0084] In a nitrogen atmosphere, 1 kg of 1800 m 2 / g, pore volume is 0.85cm 3 / g porous carbon material was placed in a deposition furnace for CVD deposition, monosilane gas was introduced, the flow rate of monosilane was 3L / min, the deposition temperature was 500°C, and the deposition time was 219min to obtain the inner core.
[0085] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 84 min to obtain a silicon-carbon negative electrode material.
[0086] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, and the mass fraction of silicon is 45%.
[0087] Comparative Example 2
[0088] In a nitrogen atmosphere, 1 kg of 1800 m 2 / g, pore volume is 0.85cm 3 / g of porous carbon material was placed in a deposition furnace for CVD deposition, and a mixed gas of monosilane and germane was introduced, with a flow rate of 3 L / min for monosilane and 0.29 L / min for germane. The deposition temperature was 500°C and the deposition time was 176 min to obtain an inner core.
[0089] Then, acetylene gas was used with a flow rate of 3 L / min, and deposition was carried out at 620°C for 84 min to obtain a silicon-carbon negative electrode material.
[0090] In the silicon-carbon negative electrode material obtained in this embodiment, the mass fraction of the carbon coating layer is 3%, the mass fraction of the silicon-germanium alloy is 45%, and the mass ratio of silicon to germanium in the silicon-germanium alloy is 80:20. Figure 2 As shown, there are obvious germanium agglomerates in the silicon-germanium alloy.
[0091] Test Case
[0092] Weigh 320 mg of the silicon-carbon negative electrode material prepared in the above examples and comparative examples, 40 mg of conductive carbon black and 40 mg of carboxymethyl cellulose, add appropriate amount of deionized water and use a planetary ball mill for 2 h, apply the milled slurry on a copper foil current collector, and cut it into a negative electrode sheet with a diameter of 12 mm after vacuum drying at 80 ° C for 12 h, with a loading of 2.5 mg / cm 2 .
[0093] Then, metallic lithium was used as the counter electrode and reference electrode, PP membrane was selected as the diaphragm, LiPF6 with a concentration of 1 mol / L was used as the electrolyte, and the solvent was a mixed solution of diethyl carbonate and ethylene carbonate with a volume ratio of 1:1. The button battery was assembled in a glove box with an argon atmosphere.
[0094] The silicon-carbon negative electrode materials obtained in the above examples and comparative examples were tested for conductivity, and the button-type batteries assembled above were tested for performance. The results are shown in Tables 1 and Figure 3 shown.
[0095] Table 1
[0096]
[0097] As can be seen from Table 1, the conductivity of the silicon-carbon negative electrode after doping with germanium is improved, and the cycle stability and rate performance are also improved. In addition, it can be seen from the comparative example and comparative example 2 that the symbiotic reaction using germanium chloride as the germanium source allows silicon and germanium to be mixed evenly, which is beneficial to improving the effect after doping with germanium. At the same time, it can be seen from the comparative example that the conductivity, cycle performance and rate performance of the silicon-carbon negative electrode material can be adjusted by adjusting the mass fraction of the silicon-germanium alloy in the silicon-carbon negative electrode material and the mass ratio of silicon to germanium.
[0098] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0099] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises a core and a carbon coating layer coating the core, wherein the core comprises a porous carbon skeleton and a silicon-germanium alloy distributed in the porous carbon skeleton, and the silicon-germanium alloy does not contain germanium agglomerates.
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The mass ratio of silicon to germanium in the silicon-germanium alloy is 20:80-99.5:0.
5.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The mass fraction of the silicon-germanium alloy in the silicon-carbon negative electrode material is 20%-70%; And / or, the mass fraction of the carbon coating layer in the silicon-carbon negative electrode material is 1%-10%.
4. The silicon-carbon negative electrode material according to claim 1, characterized in that: The specific surface area of the porous carbon skeleton is 300 m 2 / g-2500m 2 / g, pore volume is 0.4m 3 / g-1.5cm 3 / g.
5. A method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The porous carbon skeleton is subjected to vapor deposition in an atmosphere containing a silicon source and a germanium source to obtain an inner core, wherein the germanium source comprises at least germanium chloride; The core is carbon coated to obtain a silicon-carbon negative electrode material.
6. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The silicon source is selected from silane; And / or, the germanium source is selected from germanium chloride, or, the germanium source is selected from germanium chloride and germane.
7. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The temperature of the vapor deposition is 300°C-700°C.
8. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The inner core is carbon coated by chemical vapor deposition, wherein in the step of chemical vapor deposition, the gaseous carbon source is selected from at least one of acetylene, ethylene, propylene, methane and ethane, and the temperature of chemical vapor deposition is 500°C-1000°C.
9. A negative electrode sheet, characterized in that: The negative electrode active material of the negative electrode sheet is the silicon-carbon negative electrode material according to any one of claims 1 to 4.
10. A secondary battery, characterized in that: The secondary battery uses the negative electrode sheet according to claim 9.
Citation Information
Cited By
Metal-doped silicon-carbon negative electrode material and preparation method thereof
CN120319791A
Metal-doped silicon-carbon negative electrode material and preparation method thereof
CN120319791B